Study on Autopsy Cases of Suspected Poisoning Victims in an Urban Medical College Morgue - Ahmad, M; Mazumder, MRU; Al-Azad, MAS; Rahman, FN; Rahman, MM (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i1.13540 JAFMC Vol.8(1) 2012 pp.46-52